2015
DOI: 10.2217/pmt.15.46
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Interventional Procedures for Chronic Pain Management

Abstract: Ultrasonography has multiple advantages over traditional radiologic imaging modalities when used for interventional procedures. It allows improved visualization of the anatomy while avoiding ionizing radiation and risks associated with contrast use. It has proved superiority at accuracy of delivery and procedural effectiveness over blind procedures when used in association with interventional pain procedures. Although limited in its ability to see through bony structures, ultrasound has utility in visualizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 73 publications
0
17
0
6
Order By: Relevance
“…Our findings are consistent with the conclusions of previous reports. [12][13][14][15][16] The results of this study also showed that the PRI and PPI scores, two quantitative pain indexes, were significantly lower in both groups after treatment (P < 0.05), and the effect was better in the study group than in the control group.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our findings are consistent with the conclusions of previous reports. [12][13][14][15][16] The results of this study also showed that the PRI and PPI scores, two quantitative pain indexes, were significantly lower in both groups after treatment (P < 0.05), and the effect was better in the study group than in the control group.…”
Section: Discussionmentioning
confidence: 73%
“…The use of ultrasound-guided cervical nerve root injection for cervical spondylosis and the use of fistula injection for lumbar disc herniation reportedly have very high effectiveness. [11][12][13][14][15][16] In total, 60 patients were enrolled in the present study. The evaluation indicators included the operation time, VAS scores, rate of excellent JOA scores, and incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
“… 22 A regenerative solution of dextrose solution (prolotherapy) or platelet-rich plasma with US-guided procedures can significantly reduce chronic musculoskeletal pain. 23 , 24 …”
Section: Suggestions For Acute Musculoskeletal Pain Management Durmentioning
confidence: 99%
“…14 In a review, it has been emphasized that the employment of injections into these nerves with the guidance of ultrasonography (US) would increase the success rate. 15 US has been gaining popularity in the diagnosis and monitoring of several peripheral and central system disorders as a portable, non-invasive, radiation-free, less expensive and easily accessible tool. 16 US is currently used as a guide during invasive interventions into the musculoskeletal system, with the aim being to avoid the risk of iatrogenic complications due to blind injections.…”
mentioning
confidence: 99%